New directions in human information behavior (Springer, 2006)
New Directions in Human Information Behavior, co-edited by Drs. Amanda Spink and Charles Cole provides an understanding of the new directions, leading edge theories and models in human information behavior. Information behavior is conceptualized as complex human information related processes that are embedded within an individual’s everyday social and life processes.The book presents chapters by an interdisciplinary range of scholars who show new directions that often challenge the established views and paradigms of information behavior studies. Beginning with an evolutionary framework, the book examines information behaviors over various epochs of human existence from the Palaeolithic Era and within pre-literate societies, to contemporary behaviors by 21st century humans. Drawing upon social and psychological science theories the book presents a more integrated and holistic approach to the understanding of information behaviors that include multitasking and non-linear longitudinal processes, individuals’ information ground, information practices and information sharing, digital behaviors and human information organizing behaviors. The final chapter of the book integrates these new approaches and presents an overview of the key trends, theories and models for further research.This book is directly relevant to information scientists, librarians, social and evolutionary psychologists. Undergraduate and graduate students, academics and information professionals interested in human information behavior will find this book of particular benefit